INVESTIGATION OF ELECTRONIC AND MOLECULAR PROPERTIES OF 5-(3- METHYL-3-PHENYLCYCLOBUTYL)-N-PHENYL-3,6-DIHYDRO-2H-1,3,4-THIADIAZIN-2- IMINE BY EXPERIMENTAL AND THEORETICAL METHODS - Ferah, Buse; Yılmaz, Ibrahim; Dinçer, Muharrem; Çukurovalı, Alaaddin (My University, 2017)
In this work, 5-(3-methyl-3-phenylcyclobutyl)-N-phenyl-3,6-dihydro-2H-1,3,4-thiadiazin-2-imine (C20H21N3S), MPDT, wasprepared and characterized by X – ray single crystal diffraction and IR and 13C-NMR spectroscopic techniques. The moleculargeometry, vibrational frequencies, gauge including atomic orbital (GIAO) 13C chemical shift values of MPDT in the groundstate have been calculated by using the Hartree-Fock (HF) and Density Functional Theory (B3LYP) with 6-31G(d) basis set.The scaled B3LYP/6-31G(d) results shows the best agreement with the experimental values over the other method. B3LYP isapplied to explore the Mulliken atomic charges of the title molecule. In addition to frontier molecular orbital (FMO) andmolecular electrostatic potential (MEP) of the title molecule have been calculated by using the HF and B3LYP with 6-31G(d)basis set.
Keywords: Kimya; Organik; Fizikokimya